Effect of sulfur on nitrogen-containing plasma polymers in promoting osteogenic differentiation of Wharton’s jelly mesenchymal stem cells - Siow, Kim Shyong; Arifah Rahman,; Amnani Aminuddin,; Ng, Pei Yuen (Penerbit Universiti Kebangsaan Malaysia, 2021)
The role of sulfur and its synergistic effects with nitrogen moieties in mediating stem cell proliferation and differentiation has become of interest to the tissue engineering community due to chemical similarities with the glycosaminoglycans found in human tissues and cells. Glycosaminoglycans are biomolecules known to influence stem cell differentiation, but the roles of sulfur with different oxidation states on nitrogen-containing polymers have not been fully understood nor investigated. In this study, we used the plasma polymerization of 1,7-octadiene (ppOD), n-heptylamine (ppHA), ppHA grafted with vinyl-sulfonate via Michael-type addition (ppHA-SO3 ), thiophene (ppT), and ppT with air plasma treatment (ppT-air) to produce controlled amounts of nitrogen and sulfur moieties having different oxidation states, as confirmed by x-ray photoelectron spectroscopy. Assays of the proliferation and osteogenic activities of Wharton’s jelly mesenchymal stem cells (WJ-MSCs) showed the highest activities for ppHA, followed by ppHA-SO3 , due to high percentages of amines/amides and the absence of SO3 moieties in ppHA. Other plasma polymers showed less proliferation and osteogenic differentiation than the positive control (glass substrate); however, WJ-MSCs grown on ppT-air with its high percentages of SO4 displayed cytoskeletons intensified with actin stress fiber, unlike the thiol-dominated ppT. Finally, the presence of methyl groups in ppOD severely limited WJ-MSCs proliferation and differentiation. Overall, these results confirm the beneficial effects of amine/amide groups on WJ-MSCs proliferation and osteogenic differentiation, but the combination of these groups with sulfur of various oxidation states failed to further enhance such cellular activities.